First-line therapy in HER2 positive metastatic breast cancer: is the mosaic fully completed or are we missing additional pieces?. Issue 1 (December 2016) - Fabi, Alessandra; Malaguti, Paola; Vari, Sabrina; Cognetti, Francesco
Abstract The discovery of human epidermal growth factor receptor 2 (HER2) and its role in the biology of breast cancer and the subsequent development of HER2-targeted therapies, have dramatically improved clinical outcomes for women with early-stage and advanced HER2-positive breast cancer (BC). HER-2 targeted therapies represent a major step forward in achieving the goal of delivering individualized targeted therapy for BC, and trastuzumab was the first anti-HER-2 strategy to be approved for treatment of HER-2 positive BC. This review discusses the treatment of metastatic HER2-positive BC and describes efficacy and safety of novel anti-HER2 target therapies in first-line metastatic settings and the future challenges include refining such treatments, reducing toxicity and simultaneously developing innovative therapies. Furthermore, combinations of trastuzumab and drugs targeting the downstream pathway are described. In the next future will be possible to use an ample armamentarium of combination therapies directed against HER2 and key signaling components integrated in the HER network. This approach will allow clinicians to tailor the management of the individual patient on the basis of tumor- specific biomarker profiles. There is an urgent need for prospective biomarker-driven trials to identify patients for whom targeting is cost-effective.